Web-Based Information System for Laundry Services: An Extreme Programming Approach to Digital Transformation - Mgs Gustriawan Candra; Maria Ulfa; Evi Yulianingsih (Journal of Information System and Artificial Intelligence, 2026)
The rapid growth of digital technologies has accelerated the transformation of small and medium-sized enterprises (SMEs), including service-based industries such as laundry businesses. However, many of these businesses still rely on manual processes, which often result in inefficiencies and limited customer engagement. This study aims to develop a web-based information system for laundry services using the Extreme Programming (XP) methodology to support digital transformation. The development process consisted of four stages: planning, design, coding, and testing, carried out iteratively with continuous stakeholder involvement. Key features implemented include customer registration, order management, real-time order tracking, invoice generation, and administrative reporting. Functional testing confirmed that all core features performed as expected. Usability evaluation using the System Usability Scale (SUS) produced an average score of 82.3, indicating Excellent usability. Customers appreciated the mobile-first design and order tracking, employees highlighted the efficiency of order input, and administrators valued reporting functions. The findings demonstrate that XP enables rapid development, enhances system quality, and aligns software outputs with user needs. This study contributes to the literature by showing how agile methods can accelerate digital transformation in SMEs, while also offering practical implications for improving operational efficiency and customer satisfaction in the laundry service sector